Moderating Profitability in Funding Decisions on Company Value - morriz maury (Value Relevance: Jurnal Akuntansi, 2024)
Company value is an essential concept for investors because it is an indicator for assessing the company. A profitable company that can manage its funds will determine its existence in the capital market. This research is explanatory quantitative research with hypothesis testing using secondary data from Garment and Textile sector companies in Indonesia, with an observation period of 2018-2022. This research uses a purposive sampling technique with criteria and considerations determined by the researcher so that the samples that fall within these criteria are 105 samples—data collected using documentation studies through annual reports published on the Indonesian Stock Exchange. The research data analysis method uses multiple regression test analysis. The research results found that profitability could moderate the relationship between funding decisions and company value with a significant % model contribution of 3.8%.